IDENTIFYING THE EFFECTS OF PETROLOGIC PROCESSES IN A CLOSED BASALTIC SYSTEM USING TRACE-ELEMENT CONCENTRATIONS IN OLIVINES AND GLASSES: IMPLICATIONS FOR COMPARATIVE PLANETOLOGY - Hagerty J.J.; Shearer C.K.; Burger P.V.; Vaniman D.T. (My University, 2006)
We use trace-element concentrations in olivines and glasses from a closed basaltic system to identify the effects of petrologic processes on the trace-element record of that system. The closed basaltic system in question is the Makaopuhi Lava Lake (MLL), which is closed with respect to magma mixing. Detailed studies of this lava lake have provided important information about system variables and petrologic processes that have been measured and observed at the lake. These previous studies show that olivine crystallized from the lava lake at all stages of the lake's evolution, which means that olivine and residual glasses contain a record of the lake's petrologic history. We use this information, in conjunction with variations in trace-element concentrations in olivines and glasses, to show that mineral crystallization, gravitational settling, convective flow, filter pressing, and mineral-melt interface kinetics have characteristic effects on the trace element record of a closed basaltic system. These results are pertinent to the field of comparative planetology because they can be used to evaluate petrologic information in small samples from other planetary bodies, where information about system variables and/or petrologic processes is limited.
Keywords: BASALT; COMPARATIVE PLANETOLOGY; DISTRIBUTION COEFFICIENTS; GEOCHEMISTRY; GLASS; HAWAII; MAKAOPUHI LAVA LAKE; OLIVINE; TRACE ELEMENTS AND REE